2019
DOI: 10.1177/0956462419830232
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the spatial relationship between primary road distance to antenatal clinics and HIV prevalence in pregnant females of Lilongwe, Malawi

Abstract: While urbanization in a sub-Saharan African (SSA) context can lead to greater independence in women, various sociological, biological, and geographical factors in urban areas may keep women at a higher risk for HIV than men. Access to major roads during Malawi’s transition into rapid urbanization may leave women disproportionately vulnerable to HIV infection. It is not well established whether women who report to health clinics closer to major roads have higher or lower levels of HIV. In this study we explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…There could be many factors affecting the clustering of HIV recent infections, such as local HIV burden, population density, traffic convenience, social culture, public health policies, etc. ( 18 , 19 ). For areas with significant increase of recent infections, proper public health policies should be in place to curb the ongoing spread of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…There could be many factors affecting the clustering of HIV recent infections, such as local HIV burden, population density, traffic convenience, social culture, public health policies, etc. ( 18 , 19 ). For areas with significant increase of recent infections, proper public health policies should be in place to curb the ongoing spread of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of municipal services, such as waste disposal, can also have an impact; studies have demonstrated increased risk of dengue virus exposure in households closer to dumpsters [21]. Greater distances to health care facilities were also shown to be associated with higher burdens of malaria in urban environments [14], while closer distances [107] or proximity to major roads [63] were associated with reduced risk of HIV. Evidence also exists that women living in urban neighborhoods near a market may be at an increased risk of HIV infection [107].…”
Section: Municipal Servicesmentioning
confidence: 99%